Dynamika vybraných biochemických ukazatelů energetického metabolismu u telat pri dvou odlisných způsobech mlécné výzivy - Dvorák, R; Jagos, P; Skrivánek, M (Veterinarni medicina, 1986)
The effect of two milk diets on the changes in selected parameters of energy metabolism was studied in calves. After the termination of colostrum feeding, the experimental group of calves (n = 10) was given whole milk whereas the calves in the control group (n = 10) were given the Laktosan milk replacer. Blood was collected for biochemical investigation from the third day of age (determination of glucose concentration) and from the fourth week of age (evaluation of the parameters of lipid metabolism). The plasma concentrations of glucose were about the same in both groups of calves throughout the period of study. The total lipid, total cholesterol and triglyceride levels in blood serum were significantly higher in the calves of the experimental group during the milk feeding period; later they did not differ significantly from the values determined in the control calves. On the other hand, the concentrations of non-esterified fatty acids were higher in the calves of the control group in the milk feeding period; the differences, however, are not statistically significant. The average daily weight gains from the 5th to the 18th week of age were significantly higher in the calves given whole milk.
Keywords: Lipids; Fatty Acids, Nonesterified; potrava speciální; kyseliny mastné neesterifikované; lipidy; Animal Feed; Animals; Body Weight; tělesná hmotnost; Cattle; krmivo pro zvířata; mléko; Food, Formulated; zvířata; krevní glukóza; Blood Glucose; Milk; skot